Trends and features in sustainable construction materials; a global review - Din, Khalid Mehmood Sadar; Ishak, Md Sayuti (Archives of Civil Engineering, 2026)
Building construction projects are one of the major consumers of natural resources, causing resource depletion and the emission of environmental pollution. The sustainability parameters in construction are shifting the paradigm of traditional construction towards a more sustainable construction. Sustainable construction materials are designed and aligned to enhance structural durability, prevent exhaustion of natural resources, improve energy efficiency, lower harmful emissions, and enrich indoor air quality. The objective of this study is to explore the core features which drive sustainable construction materials in the building construction industry; to analyze current trends and preferences being made, and the advancement and challenges encountered in different regions worldwide. A comprehensive literature review approach is utilized to collect and synthesize data from a wide range of resources. The study includes research articles from 2014 till 2024 published in USA, Europe, and Asian countries, using search engine scopus, web of science, and google scholar, which discuss the environmental, social, and economic parameters of sustainable construction materials while excluding articles focusing exclusively on the non-construction industry. The literature review compares trends in sustainable construction materials, featuring different regions of the word. The review has identified several key features and trends shaping the construction industry towards a more sustainable construction world. It also provides a road map for industry players interested in incorporating green materials in construction works.